The Voice of Youth in Democracy: An Analysis of Generation Z's Engagement in the 2024 Regional Elections - Asmawi, Muhammad; Devi, Lathifah Sandra (Jurnal Hukum Replik, 2024)
This study aims to analyze the involvement of Generation Z in the organization of the 2024 Regional Elections in Serang Regency, focusing on their participation as members of the District Election Committee. Generation Z is known for its unique characteristics in political and democratic participation, marked by a strong desire to contribute to social change, particularly through electoral engagement. Data reveals that 45% of District Election Committee members in Serang Regency come from Generation Z, indicating their significant interest in the democratic process. Their involvement not only enhances transparency and accountability but also introduces fresh and dynamic perspectives that enrich local democracy. However, Generation Z faces various challenges, including a lack of comprehensive political education and limited understanding of election regulations. Despite these challenges, their high motivation, supported by broad access to information through social media and community backing, drives their active participation. Moreover, training provided by the government and election organizers improves their technical skills in fulfilling their roles. In conclusion, with proper support, Generation Z holds great potential to contribute to more transparent, accountable, and participatory elections in Indonesia.Generation Z, Civic Participation, and the 2024 Elections